Risky consumption of alcohol and drugs among employees at ski resorts. Issue 3 (June 2017) - Warne, Maria; Sinadinovic, Kristina; Berman, Anne H; Källmén, Håkan; Vinberg, Stig
Aim: To evaluate risky consumption of alcohol and drugs among Swedish men and women who are employed at ski resorts. Methods: A cross-sectional sample of 611 employees in 48 small and medium-sized enterprises responded to a questionnaire covering alcohol and drug use, social aspects around work and working conditions. Consumption of alcohol and drugs in the study sample was compared to population data. Data were analysed using Mann–Whitney U-tests and logistic regression analyses. Results: Compared to the general population, the study group of ski resort employees had higher scores on the Alcohol Use Disorders Identification Test (AUDIT) in all age groups except 35+ for men. Regarding the Drug Use Disorders Identification Test (DUDIT) scores, only men in the 18–24 age group had higher scores compared to the general population. The prevalence of risky alcohol and drug use was higher among seasonally employed individuals; 82.9%, compared to 58.0% among other employees for alcohol; 8.3% compared to 2.8% for drugs. The regression analysis indicated that social aspects such as living together with colleagues and having co-workers/friends who are frequently inebriated were the most significant explanatory variables for explaining risk consumption of alcohol ( OR 16.82 and OR 4.33). Risky use of drugs was associated with being younger ( OR 0.15) and male ( OR 0.86), as well as with having co-workers/friends who are frequently inebriated ( OR 4.25). Conclusions: The study showed a high prevalence of risky alcohol consumption among ski resort employees compared to the general population, with higher risky drug consumption found only among younger men. Social aspects such as living with colleagues and having co-workers or friends who are often inebriated, were identified as important explanatory factors. Preventive measures should be introduced, targeting norms and work culture surrounding alcohol and drug use among ski resort employees.